Strategies to Overcome Homeless and Beggars with A Collaborative Approach in Makassar City - Kamrin Kamrin (Jurnal Indonesia Sosial Sains, 2024)
This research aims to provide an overview of the phenomena and opportunities for dealing with homeless and beggars in the city of Makassar, to further formulate a coping model through the formulation of effective policies, strategies and countermeasures. One of the crucial problems that the Indonesian government has been facing is the existence of homeless people and beggars, which are increasingly serious to overcome. This problem that sometimes has a relationship with the culture in one area is indeed a kind of virus or a disease that often recurs. The strategy to deal with vagrants and beggars that has been carried out by the Makassar City Government through the leading sector of related agencies has not been effective in solving the problem of vagrants and beggars. Then through exploratory data analysis, this research formulates an approach as an alternative solution to overcome homeless and beggars in the city of Makassar, by developing a holistic approach in the form of collaborative synergy between the government and the private sector.